2011
DOI: 10.1074/mcp.m111.007963
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Screen for Neurospora crassa Transcription Factors Regulating Glycogen Metabolism

Abstract: Transcription factors play a key role in transcription regulation as they recognize and directly bind to defined sites in promoter regions of target genes, and thus modulate differential expression. The overall process is extremely dynamic, as they have to move through the nucleus and transiently bind to chromatin in order to regulate gene transcription. To identify transcription factors that affect glycogen accumulation in Neurospora crassa, we performed a systematic screen of a deletion strains set generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…pacc gene in N. crassa (ORF NCU00090) is the pacc /RIM101 orthologue, extensively studied in A. nidulans and S. cerevisiae [146]. The transcription factor PacC responds to changes in extracellular pH by activating specific alkaline genes and repressing specific acid genes [147, 148]. …”
Section: Regulation Of Production Of Cellulases and Hemicellulases Inmentioning
confidence: 99%
See 2 more Smart Citations
“…pacc gene in N. crassa (ORF NCU00090) is the pacc /RIM101 orthologue, extensively studied in A. nidulans and S. cerevisiae [146]. The transcription factor PacC responds to changes in extracellular pH by activating specific alkaline genes and repressing specific acid genes [147, 148]. …”
Section: Regulation Of Production Of Cellulases and Hemicellulases Inmentioning
confidence: 99%
“…xlr-1 encodes a member of a TF family containing conserved fungal Zn(2)-Cys(6) binuclear cluster domain with significant amino acid homology to xyr1 in Trichoderma species [148], sharing 57.6% identity with homolog in T. reesei . Recently, Sun et al [143] demonstrated that a deletion of xlr-1 gene abolishes growth of N. crassa in both xylan and xylose containing media, but it slightly affects the growth on Avicel and the production of cellulase activity in the presence of this substrate.…”
Section: Regulation Of Production Of Cellulases and Hemicellulases Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of certain regulatory proteins or some key transcription regulator factors causes this difference in target protein expression [51, 52]. Gene expression and regulation studies conducted on filamentous fungi have suggested that, most of the genes encoding for the cellulose and hemicellulose degrading enzymes were majorly regulated during transcriptional stages [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Trehalose and glycogen accumulation in microbial cells when they are subjected to unfavourable growth conditions could also be used as stress indicators (Parrou et al, 1997;Türkel, 2006;Ocón et al, 2007;Iturriaga et al, 2009;Gonçalves et al, 2011). Both carbohydrates are important storage compounds in fungal vegetative cells and spores (Robinson, 2001;Rúa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%